Creep and Wear in Vitamin E-Infused Highly Cross-Linked Polyethylene Cups for Total Hip Arthroplasty: A Prospective Randomized Controlled Trial. (17th January 2018) - Rochcongar, G.; Buia, G.; Bourroux, E.; Dunet, J.; Chapus, V.; Hulet, C.
Abstract : Background: Aseptic loosening, the most common indication for revision surgery in total hip arthroplasty, can result from osteolysis caused by polyethylene (PE) wear particles. PE wear is increased by age-related oxidation of PE and free radicals emerging during irradiation cross-linking. Diffusion of vitamin E into PE stabilizes free radicals to maintain the biomechanical properties of PE. The purpose of this study was to determine whether vitamin E-infused highly cross-linked PE cups could reduce wear rates. Methods: We performed a prospective randomized controlled trial, in which 62 patients were allocated to 2 groups: a study group that received a vitamin E-infused highly cross-linked PE (HXLPE/VitE) cup and a control group that received an ultra-high molecular weight PE (UHMWPE) cup. Using radiostereometric analysis, we measured the penetration of the femoral head into the cup 7 days after surgery (baseline) and then again at 6 months and at 1, 2, and 3 years later. Results: Baseline variables did not differ significantly between the groups. At 1, 2, and 3 years after surgery, the HXLPE/VitE cup showed significantly less cumulative penetration (creep and wear) than the UHMWPE cup (p = 0.004, p < 0.0001, and p < 0.0001, respectively). The cumulative penetration after 3 years was 0.200 mm for the HXLPE/VitE cup versus 0.317 mm for the UHMWPE cup (p < 0.0001). From 1 to 3 years after surgery, after creep had stabilized and further penetration was mainly due to wear, the mean penetration increased only 0.04 mm in the HXLPE/VitE cup and 0.116 mm in the UHMWPE cup. Conclusions: Our results confirm that wear rates over the first 3 years following surgery were lower in HXLPE/VitE cups than in UHMWPE cups. This suggests that HXLPE/VitE cups may prevent osteolysis, implant loosening, and eventually revision surgery. Long-term follow-up data continue to be collected to confirm these findings. Level of Evidence: TherapeuticLevel I . See Instructions for Authors for a complete description of levels of evidence.